2017
DOI: 10.1007/s11095-017-2255-7
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacokinetic and Tissue Distribution Profile of Long Acting Tenofovir Alafenamide and Elvitegravir Loaded Nanoparticles in Humanized Mice Model

Abstract: Purpose Non-adherence to the antiretroviral (ARV) regimen is a critical factor in determining efficacy of ARV drugs for pre-exposure prophylaxis (PrEP). A long-acting parenteral formulation may be an effective alternative to daily oral dosing. A pharmacokinetic and tissue distribution study of drug-loaded nanoparticle (NP) was performed in female humanized CD34+-NSG mice. Methods Mice received 200 mg/kg each of tenofovir alafenamide (TAF) and elvitegravir (EVG) as free drugs (TAF+EVG solution) or as drug loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 21 publications
(30 reference statements)
2
14
0
Order By: Relevance
“…The presence of substantially elevated IR fluorescence until the end of study (14 days post-injection) at the injection site and within clearance organs (liver and kidney) indicates at the injection site cARV NPs could act as a "cARV NP depo" inducing sustained NP release. The above observation follows the previous PK studies, reporting high cARVs concentration at the injection site and clearance organs at the terminal time-point (Prathipati et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The presence of substantially elevated IR fluorescence until the end of study (14 days post-injection) at the injection site and within clearance organs (liver and kidney) indicates at the injection site cARV NPs could act as a "cARV NP depo" inducing sustained NP release. The above observation follows the previous PK studies, reporting high cARVs concentration at the injection site and clearance organs at the terminal time-point (Prathipati et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Previous PK studies suggested that subQ injected cARV NP leads to ARVs target tissue-level significantly above the IC 90 (Mandal et al, 2017a(Mandal et al, , 2017bPrathipati et al, 2017) for all three studied ARVs. Compared to single cARV PK studies (Mandal et al, 2017a(Mandal et al, , 2017bPrathipati et al, 2017), multiple dosage of cARV NPs illustrated even higher tissue ARV levels at 22 week (2 weeks post-terminal dose, Table 2). Further, sustained non-detectable pVL (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…BIC loaded NPs (BIC NPs) were formulated using previously reported oil-in-water (o-w) emulsion method with some modifications (Destache et al, 2016;Mandal et al, 2017c;Prathipati et al, 2017). Briefly, the 5 mL DCM (organic phase) containing PLGA, PF-127 (stabilizer) and BIC at 10:10:2 (w:w:w), respectively, was added dropwise to 20 mL of 1% PVA solution (aqueous phase), under high speed continuous stirring condition.…”
Section: Bic Np Formulation and Characterizationmentioning
confidence: 99%
“…Various longacting injectable small molecule ARV agents are already in clinical trials (Spreen et al, 2013). Our research goal is to introduce long-action to conventional ARVs by fabricating single or multiple ARV (combination ARVs, cARVs) in polymeric nanoformulations as a long-acting parenteral drug delivery system for HIV treatment and prevention (Mandal et al, 2017b(Mandal et al, , 2017cPrathipati et al, 2017;Shibata et al, 2013). Our long-acting FTC NPs (Mandal et al, 2017a), TAF+FTC NPs as well as TAF+elvitegravir (EVG) NPs were efficacious as prevention regimens (Mandal et al, 2017b(Mandal et al, , 2017cPrathipati et al, 2017;Shibata et al, 2013), and TAF +FTC+EVG NPs demonstrated efficacy as chronic HIV treatment (Mandal et al, 2018) in humanized mice.…”
Section: Introductionmentioning
confidence: 99%
“…Drugs were included into the PLGA/PVA system and investigated for their long-acting potency detectable even after 14 days by a humanized mice model [121,122]. A similar approach was exploited for the incorporation of TAF and elvitegravir, an integrase inhibitor, during the fabrication of devices to be used during vaginal prevention [123,124]. The drug absorption following oral administration were also positively affected by the use of TAF/PGLA loaded NPs, as highlighted by a statistical model study [125].…”
Section: Nucleoside Reverse Transcriptase Inhibitors Nanosystemsmentioning
confidence: 99%